Nash equilibrium design and price-based coordination in hierarchical systems - Karpowicz, Michał P. (Zielona Góra: Uniwersytet Zielonogórski)
This paper deals with the problem of designing Nash equilibrium points in noncooperative games in which agents anticipate values of Lagrange multipliers coordinating their payoff functions. The addressed model of agents? interactions, referred to as the price-anticipation game, is studied within the framework of coordination and mechanism design theory for hierarchical systems.
Keywords: Nash equilibrium; coordination in hierarchical systems; decentralized control; asymmetric information